Image Detection Model for Construction Worker Safety Conditions using Faster R-CNN - Madihah Mohd Saudi; Azuan Ahmad; Ma'arof, Aiman Hakim; Saudi, Ahmad Shakir Mohd; Ali, Mohd Hanafi; Narzullaev, Anvar; Ghazali, Mohd Ifwat Mohd (Science & Information Sai Organization Ltd, 2024)
Indexed by WOS/Scopus